Landscape appreciation in the English Lake District a GIS approach (2019)
There is a well-established tradition of historical geographers using geographical information systems (GIS) to study historic landscapes and, particularly, landscape transformation (see Cunfer 2005; Donahue 2007; Walford 2018). Such studies tend to be based on quantitative sources and social science paradigms. This tendency is unsurprising, as the GIS data model is well suited to structuring analyses of quantitative sources with attribute data in tabular form linked to spatial data representing precisely located points, lines, or polygons. This chapter presents a new approach to the study of how landscapes were perceived in the past and how this changed over time. Implementing this approach requires a very different integration of GIS from the one used in previous studies because the sources involved are not quantitative: they are texts containing qualitative descriptions and, as such, need to be analysed using a mix of approaches that combine spatial analysis with close reading.